Incidence and persistence of classical swine fever in free-ranging wild boar (Sus scrofa). - Rossi, S. (Cambridge University Press, 2005)
Although veterinary authorities aim to limit persistence of classical swine fever (CSF) in wild boar (Sus scrofa), to avoid potential transmission to pigs, factors influencing CSF transmission and persistence are not clearly understood. Here we analyse incidence and persistence in a CSF epidemic that occurred in the French Vosges Forest. Higher incidence was found in large forests compared to smaller isolated ones, being highest near the starting point of the epidemic, but poorly related to the local density. We hypothesize that the spatial and social structure of wild boar populations may be responsible for this variability of incidence over space. Persistence was highest near the starting point of the epidemic and where initial density was highest. We hypothesize that persistence was favoured by the abundance of young wild boar, itself encouraged by CSF. Our results allow us to propose management measures aimed at limiting CSF persistence.